CALIBRA: A national research infrastructure for accelerator-based research and applications - Harissopulos, S.; Lagoyannis, A.; Axiotis, M.; Stamatelatos, I. (HNPS Advances in Nuclear Physics, 2020)
CALIBRA stands for Cluster of Accelerator Laboratories for Ion-Beam Research and Applications, i.e., the Research Infrastructure proposed in 2014 to the General Secretariat for Research and Technology (GSRT) in response to the call for the establishment of the Greek National Roadmap for Research Infrastructures (RI). CALIBRA is planned to be completed in phases with the first one being implemented through the homonym project that is funded by the currently running Partnership Agreement for the Development Framework (ΕΣΠΑ 2014-2020). The CALIBRA project aims at establishing and operating an accelerator-based research infrastructure open to the national and the European scientific community to conduct research at excellence level, develop innovative applications of increased socioeconomic impact, and provide highly-specialized services, unique at the country level, to the public and private sector. CALIBRA is implemented at the Tandem Accelerator Laboratory of NCSR “Demokritos”. The project had its kickoff meeting in November 2017.